Empirical Analysis of Interrelationship Between Service Quality, Consumer Involvement, and Consumer Satisfaction - Pandey, Praveen Kumar; Verma, Priti; Trayambak, Shruti (Indian Journal of Marketing, 2020)
The advent of the 21st century brought in its wake a paradigm shift in business and professional approach and attitude. The gradual increasing focus on service element along with products to differentiate from the competitors and attract and retain customers is also an important step in this direction. However, it is at its nascent stage and requires attention of researchers. In the service segment of any industry, the chain of final success consists of a series of links : service quality and customer involvement, customer involvement and emotional satisfaction, relational benefits and customer satisfaction, loyalty behaviour and satisfaction. However, though a positive association between some of these links has been acknowledged, the role of customer involvement is still a less researched area. The paper, through empirical study, intended to examine various dimensions of these relationships with reference to service quality and customer satisfaction, with the main focus on the mediating role of customer involvement between service quality and customer satisfaction. The survey was conducted through a self-administered and closed-ended questionnaire to collect experimental data related to service quality from the customers. The findings can help industries to draft an action plan for effective service delivery to customers for easy market penetration and long-term growth.